The Role of Rural Women in Developing Animal and Poultry Production in Some Villages of Menoufia Governorate, Egypt - Salem, Salem AbdelHamid; Armanous, Mervat Shehata; El-Kholy, Shimaa AbdelMageed (Journal of agricultural, environmental and veterinary sciences, 2023)
This research aimed to identify the roles played by the rural women surveyed in the development of animal and poultry production in the study, and to determine the level of these roles, and then to stand on the sources of information of the rural women, Finally determining the nature of the relationship between the studied independent variables and the role of rural women in the development of animal and poultry production in the study area.This research was conducted in the Menoufia Governorate on a random sample of 364 respondents from the overall size, and the research data was collected in a personal interview by means of a questionnaire form during the month of August 2022, and the data was processed quantitatively and analyzed statistically using the tabular presentation by frequency, percentages, the arithmetic mean, and the simple correlation coefficient, and upward multiple gradient regression (step-wise) analysis.The most important results were as follows:- The Rural women have high experience in the field of animal and poultry production by 51%, especially in the process of breeding and treatment. It was also found that about 80% of the rural women surveyed have a high level of role in raising and caring for farm animals.- The most important sources of information for the rural women surveyed are senior farmers with a weighted average of 2.4 degrees, then the veterinarian with a weighted average of 2.3 degrees, and finally neighbors, relatives and friends with a weighted average of 1.7 degrees- The most important determinants of roles were the participation of rural women in veterinary and extension activities, the availability of sources of information, and the availability of production requirements.- Among the common problems facing the rural women surveyed are the high prices of production inputs, the poor condition of the markets and their distance from the village, and the lack of awareness campaigns and veterinary guidance.- Finally, most of the proposals and solutions were to encourage the establishment of feed factories, develop livestock markets, and educate breeders about vaccination programs for livestock and methods of prevention by 100% for each of them.
Keywords: The Role; Rural Women; Development; Animal and Poultry Production